2020
DOI: 10.3390/plants9111438
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Potential of Novel Endophytic Bacillus Strains and Mediation of Plant Defense against Verticillium Wilt in Upland Cotton

Abstract: Verticillium wilt caused by Verticillium dahliae is a threatening disease of cotton, causing economic loss worldwide. In this study, nine endophytic Bacillus strains isolated from cotton roots exhibited inhibitory activity against V. dahliae strain VD-080 in a dual culture assay. B. altitudinis HNH7 and B. velezensis HNH9 were chosen for further experiments based on their high antagonistic activity. The secondary metabolites of HNH7 and HNH9 also inhibited the growth of VD-080. Genetic marker-assisted detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…To infect cotton roots favorably, V. dahliae can selectively steer the local microbiome by its effector proteins, and increasing reports have shown that the microbiome inside and outside a plant plays an crucial role in its health (Snelders et al, 2020). Bacillus species can produce some antibiotics, which can directly strangle the growth of the pathogen or induce systemic resistance in plants (Hasan et al, 2020). In our study, it was found that GN03 possess antibiotics (streptomycin, surfactin, The tree was built using a single copy homologous gene using the neighbor joining method with a bootstrap value of 1,000.…”
Section: Gn03 Inoculation Promoted Cotton Seedling Disease Resistance and The Expressing Of Disease Resistance-related Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…To infect cotton roots favorably, V. dahliae can selectively steer the local microbiome by its effector proteins, and increasing reports have shown that the microbiome inside and outside a plant plays an crucial role in its health (Snelders et al, 2020). Bacillus species can produce some antibiotics, which can directly strangle the growth of the pathogen or induce systemic resistance in plants (Hasan et al, 2020). In our study, it was found that GN03 possess antibiotics (streptomycin, surfactin, The tree was built using a single copy homologous gene using the neighbor joining method with a bootstrap value of 1,000.…”
Section: Gn03 Inoculation Promoted Cotton Seedling Disease Resistance and The Expressing Of Disease Resistance-related Genesmentioning
confidence: 99%
“…Some chemicals, such as benomyl and acibenzolar-S-methyl, seem to work for Verticillium wilt, but they are not environment friendly (Goicoechea, 2009). Therefore, application of PGPB to control this disease is a safer and better alternative to protect upland cotton from Verticillium wilt (Hasan et al, 2020). Accordingly, beneficial PGPB with inhibitory action against V. dahliae are a promising biocontrol agent for the control of cotton Verticillium wilt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These beneficial associations boost plant health and crop productivity by increasing nutrient availability, releasing plant growth-stimulating hormones, decreasing pathogen/pest-caused diseases, or improving the environmental stress resistance [ 39 ]. Antibiotics, endotoxins, bacteriocins, siderophores, hydrolytic enzymes, hydrogen cyanide (HCN), phenazine-1-carboxylic acid (PCA), 2,4-diacetylphloroglucinol (DAPG), and other secondary metabolites produced by certain rhizosphere bacteria kill pathogens, thus preventing disease development [ 39 , 43 , 44 , 47 , 49 , 50 , 51 , 52 , 53 , 54 ]. Some PGPRs utilized in the control of plant pests and diseases are discussed below.…”
Section: Rhizosphere As a Potential Reservoir Of Biopesticidesmentioning
confidence: 99%
“…Furthermore, when compared to control treatments, cotton plants treated with two Bacillus strains (HNH7 and HNH9) showed a considerable reduction in verticillium wilt severity. Moreover, the expression of some defense-related genes was significantly higher in plants treated with Bacillus strains and inoculated with VD-080 [ 54 ].…”
Section: Rhizosphere As a Potential Reservoir Of Biopesticidesmentioning
confidence: 99%